2005
DOI: 10.1161/01.hyp.0000172757.96281.bf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time of Day of Treatment on Ambulatory Blood Pressure Pattern of Patients With Resistant Hypertension

Abstract: Abstract-Patients with resistant hypertension present high prevalence of a non-dipper blood pressure pattern. Recent results indicate that non-dipping is related partly to the absence of 24-hour therapeutic coverage in patients treated with single morning doses. Accordingly, we investigated the impact of treatment time on the blood pressure pattern in 700 patients with resistant hypertension on the basis of clinic measurements who were studied by 48-hour ambulatory monitoring. Among them, 299 patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 40 publications
1
59
0
2
Order By: Relevance
“…Hermida et al reported that antihypertensive drugs given in the morning increased the prevalence of non-dipping blood pressure from 38 to 62% in resistant hypertensive patients. 26 Thus, the best method of tailoring the treatment of nondippers is a major concern of chronotherapy. Uzu and Kimura 27 reported that hydrochlorothiazide restores the diminished nocturnal blood pressure decline, and shifts circadian rhythm of blood pressure from a non-dipper to a dipper profile.…”
Section: Discussionmentioning
confidence: 99%
“…Hermida et al reported that antihypertensive drugs given in the morning increased the prevalence of non-dipping blood pressure from 38 to 62% in resistant hypertensive patients. 26 Thus, the best method of tailoring the treatment of nondippers is a major concern of chronotherapy. Uzu and Kimura 27 reported that hydrochlorothiazide restores the diminished nocturnal blood pressure decline, and shifts circadian rhythm of blood pressure from a non-dipper to a dipper profile.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial of patients with resistant hypertension (n = 250), investigators randomly assigned patients to receive one of their drugs at bedtime versus usual care. 41 Bedtime treatment resulted in a 9-mmHg drop in mean systolic blood pressure. Implications for practice are to: (1) consider using fixed combination drugs to improve adherence and potentially decrease cost, (2) include a diuretic in multi-drug regimens and diurese patients aggressively, (3) add spironolactone if needed, and (4) consider giving one drug at bedtime to improve morning blood pressure control.…”
Section: Resistant Hypertensionmentioning
confidence: 98%
“…Bedtime dosing can lower nocturnal blood pressure by 5.2 mm Hg (p < 0.001) and potentially reduce mortality and cardiovascular events by 61% (p < 0.001). 9,42,43 However, further trials are needed to confirm these findings in patients with hypertension and in those with resistant hypertension. 11…”
Section: What Modifications Are Most Likely To Be Effective?mentioning
confidence: 99%